2012
DOI: 10.1073/pnas.1216016110
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the ERAD pathway via inhibition of signal peptide peptidase for antiparasitic therapeutic design

Abstract: Early secretory and endoplasmic reticulum (ER)-localized proteins that are terminally misfolded or misassembled are degraded by a ubiquitin-and proteasome-mediated process known as ER-associated degradation (ERAD). Protozoan pathogens, including the causative agents of malaria, toxoplasmosis, trypanosomiasis, and leishmaniasis, contain a minimal ERAD network relative to higher eukaryotic cells, and, because of this, we observe that the malaria parasite Plasmodium falciparum is highly sensitive to the inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 43 publications
4
112
0
2
Order By: Relevance
“…A previously reported bioinformatic analysis concluded that p97 functions in the P. falciparum endoplasmic reticulum (ER)-associated degradation (ERAD) pathway, a streamlined protein quality-control pathway that is critical for the control of ER stress. Furthermore, pharmacologic interference with different proteins of the ERAD pathway (including p97 with DBeQ) in P. falciparum inhibits parasite growth (41). The aligned protein sequences of P. falciparum p97 (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…A previously reported bioinformatic analysis concluded that p97 functions in the P. falciparum endoplasmic reticulum (ER)-associated degradation (ERAD) pathway, a streamlined protein quality-control pathway that is critical for the control of ER stress. Furthermore, pharmacologic interference with different proteins of the ERAD pathway (including p97 with DBeQ) in P. falciparum inhibits parasite growth (41). The aligned protein sequences of P. falciparum p97 (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human SPP is involved in the maturation of the hepatitis C virus core protein [55], which is required for the production of viral particles [56,57]. In the malaria parasite P. falciparum, inhibition of SPP can block growth of the parasite [58], and may represent a future therapeutic strategy. The functions of the SPPL family members are still being uncovered [52].…”
Section: Aspartate Impsmentioning
confidence: 99%
“…Abundance of spliced cib1 mRNA increased considerably when cells were treated with the ER stress inducing compounds tunicamycin (Tm) or DTT ( Figure 1B). In addition, we found increased expression of five conserved UPR target genes upon Tm or DTT treatment: um15034, which encodes a predicted homolog of the ER-resident chaperone Karyogamy Gene2/Binding Protein1 (Bip1; e-value: 0) (herein referred to as bip1) (Normington et al, 1989;Rose et al, 1989); um00904, which encodes a predicted homolog of yeast ER chaperone Luminal Hsp70 1 (Lhs1p) (e-value: 1.0e-49); um05352, which encodes a predicted homolog of yeast protein disulfide isomerase Multicopy Suppressor of PDH1 deletion1 (Mpd1p) (e-value: 6.0e-25); um10287, which encodes a predicted homolog of the yeast glycoprotein chaperone Calnexin1 (Cne1p) (e-value: 3.0e-65) (Travers et al, 2000); and um02729, which encodes a predicted homolog of the Plasmodium falciparum signal peptide peptidase Spp1 (e-value: 3.0e-46), known to be involved in the ER-associated degradation pathway in P. falciparum, Drosophila melanogaster, and Arabidopsis thaliana (Martinez and Chrispeels, 2003;Casso et al, 2012;Harbut et al, 2012) (Figure 1B;see Supplemental Figures 3A and 3B online).…”
Section: Cib1 Is the Homolog Of The Central Upr Regulator Hac1 And Ismentioning
confidence: 99%